2018
DOI: 10.3892/ol.2018.8693
|View full text |Cite
|
Sign up to set email alerts
|

Expression of engrailed homeobox 2 regulates the proliferation, migration and invasion of non‑small cell lung cancer cells

Abstract: The present study aimed to investigate the expression, biological function and mechanism of action of engrailed homeobox 2 (EN2) in non-small cell lung cancer (NSCLC) at the tissue and cellular level. A total of 42 patients who underwent surgical resection of NSCLC tissues between January 2014 and January 2015 were included in the present study. EN2 mRNA expression levels in explanted NSCLC tissues were determined using reverse-transcription quantitative polymerase chain reaction analysis. Adenocarcinoma human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Recent studies have shown that homeobox-containing genes, including HOX, EMX, PAX, EN, and so on, as key regulators contribute to the development and progression of a variety of human cancers 3 , 18 , 19 . As the human engrailed homolog, EN2 has been reported to correlate closely with human cancers such as prostate, breast, bladder, ovarian cancer, and non -small cell lung cancer 6 – 8 , 20 , 21 . However, it remains unclear whether EN2 has any role in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that homeobox-containing genes, including HOX, EMX, PAX, EN, and so on, as key regulators contribute to the development and progression of a variety of human cancers 3 , 18 , 19 . As the human engrailed homolog, EN2 has been reported to correlate closely with human cancers such as prostate, breast, bladder, ovarian cancer, and non -small cell lung cancer 6 – 8 , 20 , 21 . However, it remains unclear whether EN2 has any role in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…EN2 is a member of the homeobox family, which encodes a homeodomain-containing transcription factor that is essential for early development. Elevation of EN2 has been highly correlated with the proliferation, invasion, and migration in several types of malignancies [18][19][20][21][22][23][24][25][26], however, controversial results show that EN2 is silenced in other cancers [27][28][29], and thus EN2 acts as a potential diagnostic and prognostic biomarker [23,[30][31][32][33]. However, decreased EN2 in renal carcinoma has been observed and downregulation of EN2 in 786-O cell line promoted proliferation and reduced apoptosis [27,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Engrailed-2 (EN2) gene encodes a homeobox-containing transcription factor and participates in the regionalization, patterning and cell differentiation in early brain development [15][16][17]. Accumulated evidence demonstrates that EN2 is highly associated with tumorigenesis in some types of cancers [18][19][20][21][22][23][24][25][26], however, controversial results show that EN2 is silenced in other cancers [27,28]. As for glioma, it remains unclear about EN2 expression pattern and potential functions.…”
Section: Introductionmentioning
confidence: 99%
“…After 6-48 hour, non-invading cells were scraped from the upper side of the insert using a cotton swab. Invading cells on the bottom of the insert were fixed and stained with Diff-Quick Stain (IMEB Inc., USA) according to manufacturer's instructions 20-22. The total number of invading cells was counted for each insert under a light microscope (Nikon Corporation, Japan).…”
Section: Methodsmentioning
confidence: 99%